Enhancing consumer attitudes toward a website as a contributing factor in business success - Alcántara-Pilar,Juan Miguel (2018)
This paper examines how consumers develop their attitude toward a destination website and are influenced by its usability, perceived risk and perceived usefulness - all of which can enhance their purchase intention. To create an authentic browsing scenario for the study, a website was specially designed for a fictitious tourist destination. Participants were invited to browse the site freely while carrying out the task assigned to them. This approach contributed added value to the research by simulating the real behavior of consumers who are faced with a range of options when selecting their purchase. The findings confirm that perceived usability and usefulness exert a positive influence on attitude toward the website, while the effect of the perceived risk is negative. The key implication is that if tourism business managers can better understand how attitude toward a website is developed this will enable them to market their products and services more effectively.